PERLINDUNGAN HUKUM BAGI PEREMPUAN KORBAN PENELANTARAN HAK NAFKAH (STUDI KASUS DI DESA NEGARARATU KECAMATAN SUNGKAI UTARA KABUPATEN LAMPUNG UTARA) - Azizah, Farokah; Setiawan, Agus; Shulton, Habib; Izza, Miftakhul (Institut Agama Islam Ngawi, 2025)
This article analyzes the form of legal protection for women who are victims of neglect of livelihood. Some societal groups still view the lack of compensation for a wife's work as merely domestic violence rather than a legal violation, leaving wives vulnerable. This study explores legal protection for divorced women under Law Number 23 of 2004 on Domestic Violence. The research, conducted in Negararatu Village, Sungkai Utara District, North Lampung Regency, employs a qualitative approach. This study utilizes three types of data sources: primary data from interviews with relevant individuals, secondary data, and tertiary data gathered through observations, interviews, documentation, and direct accounts from victims of economic neglect. Data analysis involves reduction, presentation, verification, and conclusion drawing. The study reveals that wives in Negararatu Village, Sungkai Utara District, North Lampung Regency, experience neglect of their livelihood rights. Legally, protection for victims is provided under existing regulations, including the Domestic Violence Law. The obstacle is that legal protection is not fulfilled because victims are reluctant to report to the police, considering that this case is a complaint offense, the legal protection process cannot be carried out if the victim does not report it first. Keywords: Legal Protection, Women, Livelihood, Domestic Violence.